Happydays Bakery Enterprise / Nazrul Amree Abd Shahid... [et al.] - Abd Shahid, Nazrul Amree; G.M Khalem, Shahrizman; Yusof, Mazlan; Shabudin, Shamrul Farizal; Abd Samad, Mohd Faizul (2001)
Happydays Bakery Enterprise is a partnership company that runs bread factory for supplying bread in Alor Setar ,Kedah. They started their business in 1 January 2002. The Main factory is in Alor Setar, Kedah.